High polymorphism in big defensin gene expression reveals presence–absence gene variability (PAV) in the oyster Crassostrea gigas. Issue 2 (April 2015) - Rosa, Rafael D.; Alonso, Pascal; Santini, Adrien; Vergnes, Agnès; Bachère, Evelyne
Highlights Cg-BigDefs display a high interindividual polymorphism in basal mRNA expression. All three Cg-BigDefs are not simultaneously expressed in a single oyster. Lack of Cg-BigDef mRNA expression is likely due to the absence of the corresponding gene. First report in an invertebrate of Presence–Absence Variation affecting immune genes.